ASE Spectral Slice Gain-Clamping of EDFA - Poopalan, Prabakaran; Haoken, Huoermaiti; Tamchek, Nizam; Harun, Sulaiman Wadi; Subramaniam, T.; Ahmad, Harith (Institute of Electrical and Electronics Engineers (IEEE), 2004)
An erbium-doped fiber amplifier operating in the C-band is gain clamped, at about 26 dB with noise figures below 6 dB by multiple fiber Bragg gratings. These gratings are placed at the amplifier output with center wavelengths in between communication channels so that unwanted amplified spontaneous emission is removed but put to good use. A 0.5-dB gain compression point at -15 dBm of input signal powers for two simultaneous signal channels is also demonstrated.